2015
DOI: 10.1159/000369905
|View full text |Cite
|
Sign up to set email alerts
|

Augmented Pentose Phosphate Pathway Plays Critical Roles in Colorectal Carcinomas

Abstract: Glycolysis and the pentose phosphate pathway (PPP) are preferentially activated in cancer cells. Accumulating evidence indicated the significance of the altered glucose metabolism in cancer, but the implication for oncotherapy remains unclear. Here we report that the synthesis of glycolytic and PPP enzymes is almost ubiquitously augmented in colorectal carcinoma (CRC) specimens. The mammalian target of rapamycin (mTOR) inhibitor INK128 (300 nM) and phytochemical Avemar (1 mg/ml) inhibited the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 35 publications
0
21
0
1
Order By: Relevance
“…and ), suggesting that CTOSs are more resilient against thioredoxin inhibition due to NRF2 feedback. Pharmacological inhibition of critical enzyme for PPP (G6PD) had negligible effects in terms of NRF2 feedback, with the exception of TXNRD1 induction at 24 h. Previously, we found that G6PD inhibitor CB83 reproducibly decreased NADPH/NADP + ratios, but failed to alter GSH/GSSG ratios in CRC cell lines . While the compensation mechanisms remain unknown, other NADPH production pathway could be involved in NRF2‐independent manner.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…and ), suggesting that CTOSs are more resilient against thioredoxin inhibition due to NRF2 feedback. Pharmacological inhibition of critical enzyme for PPP (G6PD) had negligible effects in terms of NRF2 feedback, with the exception of TXNRD1 induction at 24 h. Previously, we found that G6PD inhibitor CB83 reproducibly decreased NADPH/NADP + ratios, but failed to alter GSH/GSSG ratios in CRC cell lines . While the compensation mechanisms remain unknown, other NADPH production pathway could be involved in NRF2‐independent manner.…”
Section: Discussionmentioning
confidence: 92%
“…Using patient‐derived colorectal CTOSs and their xenografts , we made several discoveries. First, five GST isoforms ( GSTA1, A2, M4, O2, and P1 ) are up‐regulated in colorectal CTOSs relative to fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most types of human cancers, PPP is over-activated1819. Additionally, G-6-P dehydrogenase (G6PD) was reported to be activated by c-Src20.…”
Section: Resultsmentioning
confidence: 99%
“…Xu et al (51) provided intimated the importance of the TKT-like 1 (TKTL1; one TKT isoform) dysregulation in human HCT116 colon carcinoma cells and indicated that TKTL1 overexpression may be considered as a novel tumor marker, as well as a promising target for anticancer therapy. Furthermore, Shibuya et al (52) reported that the synthesis of glycolytic and PPP enzymes is almost ubiquitously augmented in colorectal carcinoma specimens and that pharmacological inhibition of the mechanistic target of rapamycin (mTOR)-PPP axis presents a promising therapeutic strategy against CRCs.…”
Section: Numerous Novel Glucose Metabolism Mechanisms Involve Mirna Rmentioning
confidence: 99%